Pressure vessel design manual illustrated procedures for solving major pressure vessel design problems - Moss, Dennis R. (Amsterdam ; Boston : Gulf Professional Pub., 2004)
Picking up where the success of the previous editions left off, this book is an accumulation of design procedures, methods, techniques, formulations, and data for use in the design of pressure vessels, their respective parts and equipment. It's written specifically for designers and engineers involved in designing and specifying or manufacturing of pressure vessels. The book also has broader applications to chemical, civil and petroleum engineers who construct, install or operate process facilities, and would be a valuable aid to those who inspect the manufacturing of pressure vessels or review designs. The format of this book continues to differ from most technical ones, as there are many handy visual aids throughout the text. It is not just a reference book, but a practical guideline, that aids designers and engineers to solve practically every design problem that an engineer might encounter with pressure vessels. As an easy-to-use reference, the book provides the user with a logical step by step approach to the design of ASME (American Society of Mechanical Engineers) Code vessels, such as the method for determining the Minimum Design Metal Temperature (an ASME requirement for all pressure vessels). * Covers a collection of design and analysis methods, all presented with the use of visual aides. * New edition includes 26 new procedures, giving the engineer 83 different procedures to use as tools in solving design issues. * Works not just a reference tool, but a practical guideline for every design problem.
Stresses in Pressure Vessels; General Design; Design of Vessel Supports; Special Designs; Local Loads; Related Equipment; Transportation and Erection of Pressure Vessels; Appendices A-R:Guide to ASME Section VIII, Division 1; Design Data Sheet for Vessels; Joint Efficiencies (ASME Code); Properties of Heads; Volumes and Surface Areas of Vessel Sections; Vessel Nomenclature; Useful Formulas for Vessels; Material Selection Guide; Summary of Requirements for 100% X-Ray and PWHT; Material Properties; Metric Conversions; Allowable compressure stress for columns; Flat plate formulas; External Insulation for Vertical Vessels; Flow over Weirs; Time Required to drain vessels; Vessel Surge capacities and hold up times; Minor Defects evaluation procedure.
Includes bibliographical references and index.
Keywords: Pressure vessels -- Design and construction -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc